1985
DOI: 10.1002/jmv.1890160204
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the hutchinson strain of non‐A, non‐B hepatitis virus by combined use of β‐propiolactone and ultraviolet irradiation

Abstract: A beta-propiolactone/ultraviolet irradiation procedure (beta PL/UV) has been evaluated for its ability to inactivate 30,000 chimpanzee infectious doses of the Hutchinson strain of non-A, non-B (NANB) virus. The chimpanzees were inoculated with plasma to which this dose of the titrated virus had been added prior to application of the beta PL/UV process in accordance with a procedure used for licensed blood derivatives in Germany. Neither animal developed hepatitis. When subsequently challenged with the same con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A potential contribution of hepatitis non-A, non-B virus-neutralizing antibodies to the result of this study cannot be ruled out totally, as immunoglobulins are produced from pools of more than 1, OOO donations. However, the non-P-PL-treated, spiked immunoglobulin solution (control preparation) was fully infectious, and furthermore neutralizing antibodies against hepatitis non-A, non-B virus are estimated to be very rare and have not yet been detected despite extensive search in immunoglobulins, hyperimmunoglobulins, or reconvalescent sera [Prince et al, 1985b]. We therefore assume that the inactivation of hepatitis non-A, non-B virus in this study must be caused by the 0-PL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A potential contribution of hepatitis non-A, non-B virus-neutralizing antibodies to the result of this study cannot be ruled out totally, as immunoglobulins are produced from pools of more than 1, OOO donations. However, the non-P-PL-treated, spiked immunoglobulin solution (control preparation) was fully infectious, and furthermore neutralizing antibodies against hepatitis non-A, non-B virus are estimated to be very rare and have not yet been detected despite extensive search in immunoglobulins, hyperimmunoglobulins, or reconvalescent sera [Prince et al, 1985b]. We therefore assume that the inactivation of hepatitis non-A, non-B virus in this study must be caused by the 0-PL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The chimpanzee model was used to demonstrate that blood products were often contaminated with NANBH due to the use of large pools of plasma in manufacturing. Methods to inactivate the agent in blood products and render them safe for use in humans were based on infectivity studies in the chimpanzee, including UV light in the presence of beta-propiolactone ( Prince et al 1985 ) and solvent-detergent treatment ( Horowitz et al 1993 ; Prince et al 1984 , 1987 ). Long-term follow-up of chimpanzees and patients revealed that NANBH often induced chronic or persistent infections ( Bradley et al 1981 ), highlighting the need to develop methods to detect the virus and reduced transmission.…”
Section: Discovery and Characterization Of Transfusion-associated Nonmentioning
confidence: 99%
“…28,29 The emergence of HIV and reports of non-A, non-B hepatitis transmission by some IVIG products 30,31 caused manufacturers and regulatory agencies to examine existing IVIG manufacturing procedures for their capacity to eliminate viruses. [32][33][34][35][36][37][38][39][40][41] Development of dedicated virus inactivation procedures for IVIG production was also initiated. 42,43…”
Section: Development Of Virus Elimination Proceduresmentioning
confidence: 99%